Tanggapan Responden terhadap Media Pembelajaran Visual Novel Chuumon Kudasai! - Aiman, Silmi Husniya; Arianingsih, Anisa (Mahadaya: Jurnal Bahasa, Sastra, Dan Budaya, 2025)
This study aims to determine how respondents respond to the visual novel learning media Chuumon Kudasai!. The method used in this research is the ADDIE model (Analysis, Design, Development, Implementation, Evaluation), with an online questionnaire survey used as data collection instrument, involving seven Japanese Literature students from the Universitas Komputer Indonesia in the 2021 academic year who were taking the Japanese for Tourism specialization course. The results of the study indicate that respondents provided positive feedbacks, finding the learning media interesting, easy to access, and helpful in improving their understanding of Japanese language expressions used in the restaurant industry. It is expected that this media can help students in learning Japanese used in the restaurant industry. Keywords: ADDIE, Japanese for Restaurant Industry, Learning Media, Visual Novel